Polysaccharides from Ulva prolifera O.F. Müller inhibit cell proliferation via activating MAPK signaling in A549 and H1650 cells. Issue 15 (16th June 2021) - Yang, Juan Juan; Wang, Ye Hua; Yin, Jiao; Leng, Hong; Shen, Song dong
Abstract : H2 O2 has recently been reported to cause a significant increase in the production and expression of matrix metalloproteinases (MMPs), which is closely correlated with lung cancer metastasis. Abstract : Reactive oxygen species (ROS), especially hydrogen peroxide (H2 O2 ), have recently been reported to cause a significant increase in the production and expression of matrix metalloproteinases (MMPs), which are closely correlated with lung cancer metastasis. The aim of the present study is to determine the inhibitory effects of a polysaccharide isolated from Ulva prolifera O.F. Müller ( U. prolifera ) on the invasive potential of non-small cell lung cancer (NSCLC) cells, and further to explore the underlying mechanisms connected to that potential. The data showed that increased MMP-9 resulting from H2 O2 exposure was mediated by activating mitogen-activated protein kinases (MAPKs). Pre-treatment with polysaccharides suppressed the activation of H2 O2 -mediated MAPK pathways and cell invasion. Hence, MMP-9 production triggered by H2 O2 was demonstrated by activating MAPK signaling in a Myc-dependent manner. Taken together, these results suggested that polysaccharides suppress H2 O2 -induced cell invasion by inhibiting Myc-mediated MMP-9 gene transcription through the MAPK signaling pathway in A549 and NCI-H1650 cells. Our data also suggested that polysaccharides may be useful in minimizing the development of lung cancer metastasis. In the future, pretreatment with polysaccharides because of their antioxidant properties might be beneficial to enhance surgical outcomes.